Millenium polskie w świetle prasy regionalnej ziem zachodnich = The Polish millennium within the light of regional press of the western territories - Krzyżanowski, Sławomir (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article raises the issue of attitude that Polish communist authorities had towards the ecclesiasticalcelebrations of the Polish millennium. It is based on the press of western territories, i. c. "Gazeta Robotnicza'' and "Słowo Polskie" from Wrocław and "Gazeta Zielonogórska" from Zielona Góra. The article debunks the propaganda activities undertaken by the communist in order to discredit the Catholic Church in the eyes of the Polish Society.
Keywords: prasa polska; czasopisma regionalne i lokalne polskie; stosunki polsko-niemieckie; list biskupów polskich do biskupów niemieckich; Chrzest Polski (966) - rocznice